2022
DOI: 10.3889/aph.2022.6046
|View full text |Cite
|
Sign up to set email alerts
|

Phonological awareness in children with developmental language disorder

Abstract: Children with developmetal language disorder have impaired developmental pattern of language structure. Literature data speak in favor of delay and/or difficulties in development of phonological, lexical, morphological and syntactic structure, but the nature of developmental language disorder (DLD) has still not been elucidated. The aim of this paper was to present and analyze data about phonological awareness in children with DLD based on a systematic literature review. Also, we wanted to point out some metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Research have found some phonological issues in productive phonology such as omissions of unstressed syllables and final consonants and changing syllabic structures (e.g., omitting final consonants and reducing consonant and vowel clusters; Aguilar-Mediavilla et al, 2002 , 2007 ; Bishop and Clarkson, 2003 ; Gallon et al, 2007 ; Broc et al, 2013 ; Larkin et al, 2013 ). Additionally, children with DLD struggle with other phonological abilities, such as in phonological awareness abilities including complex tasks like deleting phonemes, substituting phonemes, or producing rhyming words ( Thatcher, 2010 ; Vukovic et al, 2022 ; Korlaet et al, 2023 ). A considerable body of research has focused on studying morphological problems in children with DLD.…”
Section: Introductionmentioning
confidence: 99%
“…Research have found some phonological issues in productive phonology such as omissions of unstressed syllables and final consonants and changing syllabic structures (e.g., omitting final consonants and reducing consonant and vowel clusters; Aguilar-Mediavilla et al, 2002 , 2007 ; Bishop and Clarkson, 2003 ; Gallon et al, 2007 ; Broc et al, 2013 ; Larkin et al, 2013 ). Additionally, children with DLD struggle with other phonological abilities, such as in phonological awareness abilities including complex tasks like deleting phonemes, substituting phonemes, or producing rhyming words ( Thatcher, 2010 ; Vukovic et al, 2022 ; Korlaet et al, 2023 ). A considerable body of research has focused on studying morphological problems in children with DLD.…”
Section: Introductionmentioning
confidence: 99%